Integrating transcriptomic and metabolomic analysis in roots of wild soybean seedlings in response to low-phosphorus stress - Li, Mingxia; Zhou, Ji; Lang, Xianyu; Han, Defu; Hu, Yongjun; Ding, Yinan; Wang, Guangye; Guo, Jixun; Shi, Lianxuan (Frontiers in Plant Science, 2022)
Introduction Plants undergo divergent adaptations to form different ecotypes when exposed to different habitats. Ecotypes with ecological adaptation advantages are excellent germplasm resources for crop improvement Methods his study comprehensively compared the differences in morphology and physiological mechanisms in the roots of two different ecotypes of wild soybean (Glycine soja) seedlings under artificially simulated low-phosphorus (LP) stress. Result The seedlings of barren-tolerant wild soybean (GS2) suffered less damage than common wild soybean (GS1). GS2 absorbed more phosphorus (P) by increasing root length. In-depth integrated analyses of transcriptomics and metabolomics revealed the formation process of the ecological adaptability of the two different ecotypes wild soybean from the perspective of gene expression and metabolic changes. This study revealed the adaptation process of GS2 from the perspective of the adaptation of structural and molecular metabolism, mainly including: (1) Enhancing the metabolism of phenolic compounds, lignin, and organic acid metabolism could activate unavailable soil P; (2) Up-regulating genes encoding pectinesterase and phospholipase C (PLC) specifically could promote the reuse of structural P; (3) Some factors could reduce the oxidative damage to the membranes caused by LP stress, such as accumulating the metabolites putrescine and ascorbate significantly, up-regulating the genes encoding SQD2 (the key enzyme of sulfolipid substitution of phospholipids) substantially and enhancing the synthesis of secondary antioxidant metabolite anthocyanins and the AsA-GSH cycle; (4) enhancing the uptake of soil P by upregulating inorganic phosphate transporter, acid phosphatase ACP1, and purple acid phosphatase genes; (5) HSFA6b and MYB61 are the key TFs to resist LP stress. Discussion In general, GS2 could resist LP stress by activating unavailable soil P, reusing plant structural P, rebuilding membrane lipids, and enhancing the antioxidant membrane protection system. Our study provides a new perspective for the study of divergent adaptation of plants.